Columnar distribution of catecholaminergic neurons in the ventrolateral periaqueductal gray and their relationship to efferent pathways. Issue 2 (28th November 2012) - Suckow, Shelby K.; Deichsel, Emily L.; Ingram, Susan L.; Morgan, Michael M.; Aicher, Sue A.
Abstract The periaqueductal gray (PAG) is a critical brain region involved in opioid analgesia and provides efferents to descending pathways that modulate nociception. In addition, the PAG contains ascending pathways to regions involved in the regulation of reward, including the substantia nigra (SN) and the ventral tegmental area (VTA). SN and VTA contain dopaminergic neurons that are critical for the maintenance of positive reinforcement. Interestingly, the PAG is also reported to contain a population of dopaminergic neurons. In this study, the distribution of catecholaminergic neurons within the ventrolateral (vl) PAG was examined using immunocytochemical methods. In addition, the catecholaminergic PAG neurons were examined to determine whether these neurons are integrated into ascending (VTA, SN) and descending rostral ventral medulla (RVM) efferent pathways from this region. The immunocytochemical analysis determined that catecholaminergic neurons in the PAG are both dopaminergic and noradrenergic and these neurons have a distinct rostrocaudal distribution within the ventrolateral column of PAG. Dopaminergic neurons were concentrated rostrally and were significantly smaller than noradrenergic neurons. Combined immunocytochemistry and tract tracing methods revealed that catecholaminergic neurons are distinct from, but closely associated with, both ascending and descending efferent projection neurons. Finally, by electron microscopy, catecholaminergic neurons showed close dendritic appositions with other neurons in PAG, suggesting a possible nonsynaptic mechanism for regulation of PAG output by these neurons. In conclusion, our data indicate that there are two populations of catecholaminergic neurons in the vlPAG that form dendritic associations with both ascending and descending efferents suggesting a possible nonsynaptic modulation of vlPAG neurons. Synapse, 2013. © 2012 Wiley Periodicals, Inc.